Higher level of faecal SCFA in women correlates with metabolic syndrome risk factors - Teixeira, Tatiana F. S.; Grześkowiak, Łukasz; Franceschini, Sylvia C. C.; Bressan, Josefina; Ferreira, Célia L. L. F.; Peluzio, Maria C. G. (British journal of nutrition, 2013)
SCFA provide energy to the host and influence lipid and glucose metabolism, suggesting that they may have an impact on the occurrence of metabolic risk factors. The aim of the present study was to determine the concentration of SCFA in faeces of lean and obese individuals and to analyse whether associations between faecal SCFA and metabolic syndrome parameters are present. Lean (n 20) and obese (n 20) women of similar age (28·5 (sd 7·6) v. 30·7 (sd 6·5) years, P= 0·33) participated in the study. Anthropometric measurements, body composition, blood pressure and biochemical parameters were assessed. SCFA were extracted from faeces and quantified by GC. Blood pressure and blood glucose, although within the normal limits, were higher in the obese group compared to lean subjects (P< 0·05). Lower HDL concentration and higher insulin and homeostasis model assessment (HOMA) index were observed in the obese than in the lean group (P< 0·05). The median values of SCFA (% w/w) from the lean and obese groups were butyric (0·021 v. 0·044, P= 0·024), propionic (0·021 v. 0·051, P= 0·007) and acetic (0·03 v. 0·061, P= 0·01). SCFA correlated positively with metabolic syndrome risk factors such as adiposity, waist circumference and HOMA index (P< 0·05), and inversely with HDL (P< 0·05). Our results suggest that the higher faecal concentration of SCFA is associated with metabolic risk factors and thus may influence metabolic homeostasis.